Determinants of corporate financing decisions: A survey evidence from Czech firms - Irena Jindřichovská; Pavel Körner (Charles University in Prague, Institute of Economic Studies (IES), 2008)
This paper investigates the empirical evidence on determinants of financing decisions on the pool of respondents among financial managers of Czech firms. The theoretical section provides an overview of prominent contemporary theories on capital structure. Employing Chi-square Sign Test and Logit regression the empirical analysis provides the evidence how the financial managers perceive particular instruments of internal and external financing. We find, that firms follow pecking order theory for working capital financing, however the arguments for pecking order theory in investment financing are not that strong. Firms prefer retained earnings among internal financing instruments and bank loans and leasing among external financing instruments. Finally, the paper discusses the links with practice and some limitations of the results.
Keywords: G32; 330; corporate finance; capital structure; trade-off theory; pecking order theory; transition economies; survey; Unternehmensfinanzierung; Kapitalstruktur; Betriebliche Finanzwirtschaft; Schätzung; Tschechische Republik